New Whistle and Flute: Orchestrating Sartorial Performances of Contemporary Masculinities. (4th May 2017) - Cambridge, Nicolas
Abstract: This article addresses the shifting dynamics in sartorial culture that have contributed to constructions of masculinity in the modern period and beyond. Specifically, it examines a dominance exerted by the ubiquitous tailored suit—documenting the garment's emblematic role in geo-political contexts and its appearance in fashion's representational culture. The initial section provides a historical overview of the suit's development in the United Kingdom into a "barometer" of power relationships within the commercial and colonial arenas. The discussion goes on to consider Japan's adoption of Western-style apparel as a pivotal moment in a project of modernity undertaken during a period of socio-political upheaval in the late nineteenth century. The article then addresses the visual renegotiations of traditional understandings of masculinity conducted in certain fashion periodicals during the late twentieth and early twenty-first centuries. The conclusion suggests that these two seemingly separate strands involving the politics and poetics of sartorial culture—a paradigm shift in dress practice experienced by Japan nearly a century and a half ago, and the more recent valorization of Japanese-designed menswear by the British fashion media—have intertwined in "re-tailoring" the suit for consumption within an expanded range of sartorial constituencies in the United Kingdom.